2018
DOI: 10.1080/21691401.2018.1453830
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of microRNA 146b mimic to hepatocytes by lactosylated PDMAEMA nanoparticles for the treatment of NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases worldwide, and precision therapeutic will be a benefit for the NAFLD regression. In this study, we observed low microRNA 146 b (miR-146 b) expression in NAFLD mice model induced by methionine-choline-deficient diet (MCD) compared with control group. Furthermore, miR-146b mice induced MCD exhibited severe liver steatosis and hepatitis. A bio-distribution study showed that novel Lactosylated PDMAEMA nanoparticles effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…MicroRNAs play an important role in a variety of diseases [18][19][20] including the lipid metabolic disorder [21,22], because they can regulate a wide range of growth and development processes [7]. Recent studies indicate that miR-27a [23], miR-194 [24] and miR-146b [25] can target different genes to regulate the development of NAFLD. According to our previous research, miR-455 is the key regulator of BAT in the process of differentiation [9] and may have an effect on the regulation of lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs play an important role in a variety of diseases [18][19][20] including the lipid metabolic disorder [21,22], because they can regulate a wide range of growth and development processes [7]. Recent studies indicate that miR-27a [23], miR-194 [24] and miR-146b [25] can target different genes to regulate the development of NAFLD. According to our previous research, miR-455 is the key regulator of BAT in the process of differentiation [9] and may have an effect on the regulation of lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The immunostained sections were examined with an Olympus IX73 microscope (Olympus, Tokyo, Japan). Positive staining for a-SMA, Shh, PTH1R, PTHLH and GLI2 was semi-quantified according to a previously described method [32].…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Computer-aided quantification of the fibrotic areas was performed on Sirius Red-stained liver sections from different groups (n ¼ 5 in each group), as indicated in the relevant figure legends. The fibrotic areas were calculated according to a previously described method [32].…”
Section: Sirius Red Staining and Morphometrymentioning
confidence: 99%
“…Studies on mice and nonhuman primates suggested that an miR-33 blockade results in changes in the expression of hepatic genes involved in lipid metabolism; further, it ameliorates dyslipidemia that is induced by a high-fat diet (HFD) (Rayner et al, 2011a;Rayner et al, 2011b). However, the traditional methods used in these studies yielded a limited delivery efficacy in vivo and inhibited further applications in clinic (He et al, 2018). One of the problems associated with the low efficiency of the traditional methods is that they require high doses of agents, with mice needing 10 mg/kg of anti-miR-33 oligonucleotides per week (Rayner et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%